Spatial patterns in the retained catch composition of Irish demersal otter trawlers: high-resolution fisheries data as a management tool - Gerritsen, Hans D.; Lordan, Colm; Minto, Coilin; Kraak, Sarah B. M. (Fisheries Research, 2012)
High-resolution fisheries data from integrated logbook and Vessel Monitoring Systems (VMS) records have revealed a detailed spatial structure in the species composition of the retained catches of the Irish demersal otter trawl fleets. Hierarchical cluster analysis was used to define 8 clusters with relatively homogenous species compositions. These clusters formed 34 distinct spatial regions in the waters around Ireland. Identification of these regions can be useful for a number applications, including spatial stratification of commercial or survey data, defining and characterising fishing grounds for marine spatial planning, evaluation of closed areas and prediction of how fishing effort might be re-allocated following a closure. A case-study is presented that explores options to reduce cod (Gadus morhua) catches by implementing seasonal closures in two of the 34 regions. Cod are caught by demersal trawlers in a mixed fishery and the catches often exceed the quota, resulting in discarding of marketable fish. Two regions were identified that had relatively low effort and high cod landings. The effects of closing these regions during the first quarter of the year were explored. Cod catches were likely to be reduced by 8–22% while only 3–9% of the annual demersal otter trawl effort would be displaced. Whiting catches were also likely to be reduced, the change in catches of some other species depended on the assumed effort displacement.